The touch of the present : educational encounters, aesthetics, and the politics of the senses - Todd, Sharon (SUNY series, Transforming subjects : psychoanalysis, culture, and studies in education, 2023)
How are educational encounters understood, experienced, and lived? How are they conceptualized? How do they shape our being in and of the world? In this time of apparent distance and disconnect, this volume emphasizes the role of contact and connectedness in education, above all by understanding education as encounters, as embodied, sensory experiences. Drawing on a range of theoretical positions that highlight our profound interconnection with things and other bodies—from feminism to Buddhism to new materialism and beyond—Sharon Todd argues that educational encounters are formations of'touching'and'being touched by.'They are singular in their eventfulness and yet bring us into relation with our environment. Focusing particular attention on two key issues for teachers and students today—the climate emergency and online education—The Touch of the Present offers unique insights into the aesthetics and politics of educational practices, seeing them as embodied processes that not only contribute to how one is socialized into a given order but also carry the transformative potential for'becoming'beyond the cultural scripts we are given.
Keywords: Human body in education; Learning, Psychology of; Senses and sensation; Spatial behavior; Intersubjectivity; Liminality; ihmiskeho; oppiminen; oppimispsykologia; aistit; aistimukset; käyttäytyminen; intersubjektiivisuus; liminaalisuus